Α revision of the genus Cenopalpus in Greece (Acari: Tenuipalpidae) - Hatzinikolis Ε.Ν.; Emmanouel, N.G. (ENTOMOLOGIA HELLENICA, 1987)
The genus Cenopalpus from Greece is revised and a key to 17 species is provided, with illustrations of the nymphs. Of these species, C. bakeri Diizgiines, C. carpini (Livshitz and Mitrofanov) and C. pseudospinosus (Livshitz and Mitrofanov) are recorded for the first time from this country. A new species C. arbuti is described and illustrated. Information on the hosts, distribution data and economic importance is presented for each species. Some of the hosts and damage symptoms are recorded for the first time.